Rediscovery and redescription of Hybocodon chilensis Hartlaub, 1905 (Cnidaria: Hydrozoa) from Comau Fiord, southern Chile - Galea, Horia R. (Zootaxa, 2006)
Hybocodon chilensis Hartlaub, 1905, a poorly known species considered as of doubtful validity, is redescribed. Material examined was collected in Comau Fiord (Chile), situated a short distance from Calbuco, the original site where the type material was collected. Morphological features of living specimens of H. chilensis are fully described and illustrated, and data are provided on the cnidome. A table that compares polyp and medusa stages of species assigned to the genus Hybocodon L. Agassiz, 1862 is presented.  The systematic position of H. chilensis amongst the other members is discussed, and an identification key for the medusae is given.